2001
DOI: 10.4049/jimmunol.167.3.1413
|View full text |Cite
|
Sign up to set email alerts
|

Activating Immunity in the Liver. I. Liver Dendritic Cells (but Not Hepatocytes) Are Potent Activators of IFN-γ Release by Liver NKT Cells

Abstract: A prominent subset of the hepatic innate immune system is α-galactosylceramide (αGalCer)-reactive, (CD4+ and CD4−CD8−) CD1d-restricted NKT cells. We investigated in C57BL/6 (B6) mice which hepatic cell type stimulates hepatic NKT cell activation. Surface expression of CD1d but not CD40, CD80, or CD86 costimulator molecules was detected in hepatocytes. Pulsed in vitro or in vivo with αGalCer, hepatocytes triggered IL-4 release by liver NKT cells but required exogenous IL-12 to trigger IFN-γ release by NKT cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 69 publications
2
91
0
Order By: Relevance
“…␣-GalCer needs to be presented via CD1d on APCs to activate NKT cells (19,25,61). Because CXCL16 is expressed as a transmembrane molecule on activated DCs and macrophages (44,53), it is possible that CXCR6/CXCL16 interactions mediate cell-cell adhesion and/or provide costimulatory signals that up-regulate NKT cell function.…”
Section: Discussionmentioning
confidence: 99%
“…␣-GalCer needs to be presented via CD1d on APCs to activate NKT cells (19,25,61). Because CXCL16 is expressed as a transmembrane molecule on activated DCs and macrophages (44,53), it is possible that CXCR6/CXCL16 interactions mediate cell-cell adhesion and/or provide costimulatory signals that up-regulate NKT cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ␣-C-GalCer is able to stimulate secondary production of IFN-␥ by NK cells even though it is a weak stimulus for primary cytokine production by NK T cells (12). The downstream IFN-␥ stimulated by ␣-GalCer or ␣-C-GalCer requires the concomitant production of IL-12 (12, 23), which a number of studies suggest comes from DCs (17)(18)(19)…”
Section: Dcs Act As Apcs For Splenic But Not Hepatic Nk T Cellsmentioning
confidence: 99%
“…Fujii et al (14) showed that DCs loaded with ␣-GalCer and adoptively transferred into na ve mice stimulated a better NK T cell response in vivo than that stimulated by injection of free compound. Other studies have demonstrated the ability of ␣-GalCer to induce maturation of both splenic and hepatic DCs in vivo (15,16), and others have shown the importance of DCs as sources of ␣-GalCer-induced IL-12 (17)(18)(19).…”
mentioning
confidence: 99%
“…Consistent with studies of hepatic DCs propagated from DC progenitors in vitro, it was shown that freshly isolated liver DCs were immature, with low MHC class II and costimulatory molecule (CD40, CD80, and CD86) expression. 9 The ability of freshly isolated liver DCs to stimulate T cells has not been well defined. …”
mentioning
confidence: 99%